2021
DOI: 10.1111/bph.15428
|View full text |Cite
|
Sign up to set email alerts
|

Simultaneous targeting of oxidative stress and fibrosis reverses cardiomyopathy‐induced ventricular remodelling and dysfunction

Abstract: Background and Purpose: Oxidative stress and fibrosis are hallmarks of cardiomyopathy-induced heart failure yet are not effectively targeted by current frontline therapies. Here, the therapeutic effects of the anti-oxidant, N-acetylcysteine (NAC), were compared and combined with an acute heart failure drug with established anti-fibrotic effects, serelaxin (RLX), in a murine model of cardiomyopathy.Experimental Approach: Adult male 129sv mice were subjected to repeated isoprenaline (25 mgÁkg −1 )-induced cardia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 61 publications
2
6
0
Order By: Relevance
“…The RLX-induced blunting of LV cardiomyocyte hypertrophy that was observed in this study is somewhat consistent with previous findings demonstrating that RLX (0.5 mg/kg/day) administration alone over a 7 day period did not have a marked impact on LV cardiomyocyte size in ISO-injured mice [37], but significantly reduced LV cardiomyocyte hypertrophy in a murine model of diabetic cardiomyopathy, when continuously administered at the same dose over a 14-day period [53] in vivo. Interestingly, whilst the antagonism of P2X7R activity alone (with A-438079) also only blunted LV cardiomyocyte size after 7 days of treatment in ISO-injured mice, 16 weeks of A438079 (10 or 20 mg/kg/day) administration to mice with diabetic cardiomyopathy prevented the disease-induced increase in the HW:BW ratio and measures of hypertrophic gene expression [54].…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…The RLX-induced blunting of LV cardiomyocyte hypertrophy that was observed in this study is somewhat consistent with previous findings demonstrating that RLX (0.5 mg/kg/day) administration alone over a 7 day period did not have a marked impact on LV cardiomyocyte size in ISO-injured mice [37], but significantly reduced LV cardiomyocyte hypertrophy in a murine model of diabetic cardiomyopathy, when continuously administered at the same dose over a 14-day period [53] in vivo. Interestingly, whilst the antagonism of P2X7R activity alone (with A-438079) also only blunted LV cardiomyocyte size after 7 days of treatment in ISO-injured mice, 16 weeks of A438079 (10 or 20 mg/kg/day) administration to mice with diabetic cardiomyopathy prevented the disease-induced increase in the HW:BW ratio and measures of hypertrophic gene expression [54].…”
Section: Discussionsupporting
confidence: 92%
“…The administration of RLX and/or A4 treatment of ISO-injured mice (from days 7-14 postinjury) did not significantly affect SBP levels compared to the measurements for their saline-injected counterparts (Table 1). Consistent with previous studies [34,36,37], these findings confirmed that ISO induced fibrotic cardiomyopathy in mice, in the absence of any marked changes in SBP. Furthermore, these findings confirmed that the regulatory effects of RLX and/or A4 on measures of LV inflammation, remodelling and fibrosis were mediated independently of SBP regulation in the model studied.…”
Section: Neither Repeated Iso Administration Nor Any Of the Treatment...supporting
confidence: 92%
See 2 more Smart Citations
“…In our results, hypertrophic stimulation caused accumulation of ROS and subsequent apoptosis of cardiomyocytes; this finding is in agreement with previous studies [ 39 , 40 ]. Strategies to inhibit oxidative stress prevent the development of cardiomyopathy [ 41 , 42 ]. Research from Huang et al [ 43 ] revealed that FGF9, which shares 70% amino acid sequence similarity with FGF20, functioned as a protective factor by increasing the expression of antioxidant enzymes, which protected nigral dopaminergic neurons from MPP + -induced oxidative insult [ 34 ].…”
Section: Discussionmentioning
confidence: 99%